Alleviation of Drought Stress in Soybean by Applying a Biostimulant Based on Amino Acids and Macro- and Micronutrients - Repke, Rodrigo Alberto [UNESP]; Silva, Dayane Mércia Ribeiro [UNESP]; dos Santos, Jania Claudia Camilo [UNESP]; de Almeida Silva, Marcelo [UNESP] (MDPI, 2022)
Drought stress is one of the most predominant environmental factors hindering soybean productivity. Therefore, the study of stress-mitigating strategies, such as the use of biostimulants, is important in order to mitigate this problem. This study investigated the effects of an exogenous application of biostimulants based on amino acids and macro- and micronutrients in the physiological, biochemical and productive responses of soybean cultivated under drought stress. Treatments consisted of T1—dose 0.0 kg ha−1 (control); T2—dose 0.0 kg ha−1 (with water-deficit stress); T3—dose 0.25 kg ha−1; T4—dose 0.5 kg ha−1; T5—dose 0.75 kg ha−1; T6—dose 1.0 kg ha−1 of biostimulant. Application of T4 maintained photosynthetic metabolism, with main action on stomatal conductance, and increased the activity of antioxidant enzymes superoxide dismutase by 420%, catalase by 167% and ascorbate peroxidase by 695%. In addition, it increased the levels of proline by 106%, leaf area by 279% and the dry matter mass of the plants by 26%, which was reflected in a 22% increase in productivity. Therefore, application of the studied biostimulant at a dose of 0.5 kg ha−1 is recommended to effectively alleviate the adverse effects of drought stress on soybean.
Keywords: biostimulants; Glycine max (L.) Merrill; photosynthetic metabolism; water stress; yield